The Four Pillars of Islamic Marketing Communication Ethics: A Case Study of @jsrstore on Instagram - Yuristia Wira Cholifah; Atie Rachmiatie; Rini Rinawati; Aditya Eko Adrianto (CHANNEL: Jurnal Komunikasi, 2025)
Social media has become a space where brands express Islamic values to build trust and authenticity, raising new ethical questions about the boundary between sincere spirituality and commercial exploitation. This study investigates the ethical discourse of Islamic marketing communication on Instagram through a case study of @jsrstore, the official store of Dr. Zaidul Akbar, a prominent figure in Indonesia’s Islamic wellness movement. Drawing on Kartajaya and Sula’s four-pillar framework of Islamic marketing (teistic, ethical, realistic, and humanistic), the research analyzes how these principles are linguistically and discursively enacted in caption texts and audience interactions. Employing virtual ethnography and qualitative content analysis of 20 Instagram posts, complemented by interview data, the study reveals that @jsrstore consistently embeds spiritual intentionality (niyyah), truthfulness (ṣidq), transparency, and relational care into its digital narratives. This integration transforms commercial messaging into a form of digital da’wah, fostering trust, emotional resonance, and perceived authenticity among Muslim consumers. The findings advance Islamic communication theory by proposing a discourse-based model that transcends symbolic religiosity, demonstrating how ethical values can be performatively realized in social media branding while offering practical insights for marketers seeking to align digital engagement with Islamic ethics in Muslim-majority contexts.